The digital adoption of blockchain technology in the project management information systems: A value creation mediation model - Abeer Hmoud Al-Faouri; Sakher A. I. Al-Bazaiah; Muhammed S. Alnsour; Asma A. Abuanzeh; Muhammad Turki Alshurideh (International Journal of Data and Network Science, 2023)
Blockchain technology adoption among the businesses has become a new updated technological improvement and calls all businesses to care with it. This research aims to address its effect with project management information systems with a possible moderation effect of the value creation gained of this factor. The study used a quantitative research method to meet its objective and collected the data from Jordanian e-commerce enterprises with a total of 320 participants. PLS-SEM technique was used to perform the key analyses. The results found a significant effect of all hypothesized research assumptions and a significant moderating effect of value creation on the respective effect of study’s variables. The findings also expanded the current understanding and application of this technology and showed some implications and applicable insights that supported the existing literature and evidence in this field. The study would contribute to cover the limited research works and knowledge gaps with a suggestion to integrate this technology and application within different contextual settings.